Subjectivity, language and narration in Leylâ Erbil’s short stories - Şentürk, Semiha. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This study explores the subjectivity of characters in Leylâ Erbil's short stories and the construction of this subjectivity by the social ideology and its discourses through analyzing prominent literary genres and narration techniques in the stories. The theoretical basis of this study depends on Althusser’s and Foucault’s theories of subjectivity because the subjectivity of characters in Leylâ Erbil's short stories does not result from an essentialist and humanist basis, but they are constructed by the institutions of the state and family, and by the ideologies of religion and nationalism. Unlike the essentialist and humanist way of thinking, which attributes an essence to the individual by emphasizing its free will and self-conscious, Althusser and Foucault bring out how a human is constructed as a subject using the notions of "ideology" and "discourse." Therefore, this study argues that Leylâ Erbil by using specific narration techniques in her stories, depicts the subjectivity created by the tools of state and family, and the ideologies of religion and nationalism, and as a result implicitly criticizes the subjectivity created by these tools and ideologies by demystifying them.
Keywords: Subjectivity in literature.